The Effect of The Complexity of Tax Regulations and Principles of Justice to Taxpayer Compliance - PARWATI, Ni Made Suwitri; TOTANAN, Chalarce; MILE, Yuldi; YAMIN, Nina Yusnita; INDRIASARI, Rahayu; PAKAWARU, Muhammad Ilham; JURANA, Jurana (PT Keberlanjutan Strategis Indonesia, 2024)
Taxes are an obligation for every citizen and are a source of income for the state to finance development. This research aims to find the effect of the complexity of tax regulations and the principles of justice on taxpayer compliance. Respondents' research included 148 individual taxpayers who own businesses. The research results show that the complexity of tax regulations has a significant negative effect of -0.253 on taxpayer compliance, and 0,501, the principles of justice, have a significant positive effect on taxpayer compliance. An R square shows that independent variables will influence 45.5% on increasing taxpayer compliance. The correlation coefficient (R) is 0.674, and the degree of the relationship between all independent variables means that the correlation between the independent and dependent variables is 0.674. Based on the correlation coefficient interpretation guidelines, the relationship between the complexity of tax regulations and the principle of justice on taxpayer compliance is strong. Empirically, this research shows that the principle of justice influences taxpayer compliance, but the low complexity of tax regulations can increase taxpayer compliance. Therefore, this research implies that the government must further simplify tax regulations to encourage taxpayers to comply.